Corporate finance for lawyers : understanding the power balance between shareholders, secured lenders and unsecured creditors /: understanding the power balance between shareholders, secured lenders and unsecured creditors. (2023) - Weijs, R. J. de; (Writer on finance), Vries, Joost de; Jonkers, A. L, 1987-
No abstract available